Freedom Is a constant struggle Ferguson, Palestine, and the foundations of a movement - Davis, Angela (Tantor Media, 2016)
In these newly collected essays, interviews and speeches, world-renowned activist and scholar Angela Y. Davis illuminates the connections between struggles against state violence and oppression throughout history and around the world.
Keywords: Freedom